Resilience of Water Supply in Practice Experiences from the Frontline - Morris-Iveson, Leslie; Day, St John (IWA Publishing, 2021)
Water Resilience in Practice is co-edited by two experienced water sector professionals and reviews resilience in water supply service delivery in the form of a series of case studies from different economic contexts - ranging from low-income and fragile states to upper-income countries. It documents real experiences and reflects on the initiatives different service providers apply to strengthen resilience in practice. It describes how service providers respond, adapt, innovate and learn on an ongoing basis, and how they endeavour to meet challenges and provide water supply to users equitably and sustainably. In recent years climate resilience in water supply has been a new emerging paradigm. In response it is helpful to document and record some up-to-date experiences, which can be consolidated in one place. However, it is also necessary to recognise the multiple pressures that water resources face, such as: population growth, increased water demands, existing climatic variability as well as climate change. These pressures are having a profound impact on water supply service delivery. In this context service providers and development professionals must take active measures to respond to these risks. This book is primarily addressed to organisations and practitioners involved in planning, designing, managing and financing water supply programmes in urban and rural settings.